Reduced mortality in patients with extended duration of methadone maintenance treatment: a five-year retrospective nationwide study. Issue 3 (20th February 2023) - Huang, Chieh-Liang; Tsai, I-Ju; Lin, Wen-Chi; Lin, Cheng-Li; Ho, Ing-Kang; Wang, Ruey-Yun; Lee, Cynthia Wei-Sheng
Abstract: Background: The retention of patients under methadone maintenance treatment (MMT) is an indication for the effectiveness of the therapy. We aimed to explore the relation between mortality and the cumulative MMT duration. Methods: A retrospective cohort analysis was performed using Taiwan Illicit Drug Issue Database (TIDID) and National Health Insurance Research Database (NHIRD) during 2012–2016. We included 9149 and 11 112 MMT patients as the short and long groups according to the length of their cumulative MMT duration, 1–364 and ⩾365 days, respectively. The risk of mortality was calculated by Cox proportional hazards regression model with time-dependent exposure to MMT, and the survival probability was plotted with the Kaplan-Meier curve. Results: The mortality rates were 2.51 and 1.51 per 100 person-years in the short and long cumulative MMT duration groups, respectively. After adjusting for on or off MMT, age, sex, marital status, education level, maximum methadone dose, and comorbidities (human immunodeficiency virus, depression, hepatitis C virus, hepatitis B virus, alcoholic liver disease, and cardiovascular disease), the long group had a lower risk of death (hazard ratio = 0.67; 95% confidence interval 0.60–0.75) than the short group. Increased risk was observed in patients with advanced age, being male, unmarried, infected by HIV, HCV, and HBV, and diagnosed with depression, ALD, and CVD. Causes of death were frequently related to drug and injury. Conclusions: Longer cumulative MMT duration is associated with lower all-cause and drug-related mortality rate.